Reference intervals for 6-sulfatoxymelatonin in urine: A meta-analysis. (June 2022) - Braam, Wiebe; Spruyt, Karen
Summary: Despite the essential functions of melatonin in the human body, until now no norms of the amount of melatonin produced overnight have been established. Measuring the amount of the main urinary melatonin metabolite 6-sulfatoxymelatonin (aMT6s), corrected for creatinine, in the first morning void is the most simple as well as reliable method to evaluate the total amount of melatonin produced at night. We performed a meta-analysis to provide reference estimates and intervals by consolidating data from multiple studies. A total of 68 studies, representing 17, 847 subjects, were retained for the analysis. No gender differences could be found in aMT6s values in this meta-review. aMT6s excretion is very high during the first 5 years of life, flattens out in adolescence with gradual decline continuing to 50–60 years, after which the decline stagnates and a limited increase occurs around about 60 years of age. This late increase may suggest the premature death of individuals with low aMT6s levels, as lower aMT6s levels are found in various disorders, such as cardiovascular diseases, cancer and neurodegenerative disorders. Our aMT6s values can be used to identify individuals with a possible melatonin deficiency.